The Hidden Divide: School Segregation of Teachers in the Netherlands - Rafiq Friperson; Hessel Oosterbeek; Bas van der Klaauw (Tinbergen Institute, 2023)
We use Dutch register data to document the understudied phenomenon of teacher segregation. We show that teachers in primary and secondary schools in the four largest cities of the country – Amsterdam, Rotterdam, The Hague and Utrecht – are segregated in terms of their migration and social backgrounds. While segregation by social background is not much higher than what would be expected under random teacher-school assignment, segregation by migration background is substantial even after accounting for randomness. Relating schools' teacher composition to their student composition, we find in most cases that schools with a high proportion of teachers from a particular background tend to have a high proportion of students from that same background.
Keywords: 330